Resorbable and biocompatible glass fiber bundles having well-defined diameters and method for producing same - Patents.com
By using a two-stage nozzle design method to produce glass fiber bundles, the problems of high uniformity and defect rate of glass fibers in the prior art are solved, and the production of high-quality, uniform diameter glass fiber bundles is realized, which is suitable for composite materials in the biomedical field.
Patent Information
- Application Number
- JP2024547786
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-25
- Filing Date
- 2023-02-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to produce high-quality, uniform diameter absorbable and biocompatible fiber bundles, especially in biomedical applications, where glass fibers have higher uniformity and defect rates.
A two-stage nozzle design method is used to produce glass fiber bundles, and glass fibers are gradually formed through two continuous nozzles, thereby reducing defects and bubbles and improving the uniformity and quality of the fibers.
It has achieved the production of glass fiber bundles with uniform diameter and low defect rate, which are suitable for absorbable and biocompatible composite materials in the biomedical field.
Smart Images

Figure 2025507552000001 
Figure 2025507552000002 
Figure 2025507552000003
Abstract
Description
[Technical field]
[0001] The present invention is in the field of resorbable and biocompatible glass fiber bundles and medical devices containing glass fiber bundles for mechanical reinforcement. The invention further extends to a method for producing said glass fiber bundles. [Background technology]
[0002] Glass fibres are used in a wide variety of technical fields, including insulation, wind energy, data transmission and reinforcement materials. In the latter field, they are embedded in thermoplastic or thermosetting polymers to form composites. These composites are widely used for sports, automotive and medical applications, and in the latter field, there are many subfields in which glass fibres are used, including the above mentioned subfields to produce durable and impact-resistant materials that combine high stiffness and strength with good dimensional stability while being relatively light in weight.
[0003] Although composite materials have been present in medicine and dentistry for more than 50 years, e.g. hydroxyapatite composite resins, fiber-reinforced orthopedic implants, and more recently carbon fiber-reinforced dental implants, the field of fully resorbable composites constitutes a new class of materials. Such composites can be manufactured to be biocompatible and resorbable, and thus can contain biocompatible and resorbable glass fibers, e.g. glass fibers as disclosed in European Patent No. EP 2243749. These biocompatible and resorbable materials can be used for implants that disintegrate and are resorbed according to a controlled rate. This makes it possible to manufacture implants that do not need to be removed from the body, and therefore do not require revision surgery.
[0004] Although glass has been produced by humans for centuries, the production of high quality continuous glass fibers remains an active research field. The quality of the final product requires careful control of the raw materials and the manufacturing process. This is especially important in the case of glasses that are to be used in fully resorbable composites for biomedical applications, and thus are resorbable and biocompatible.
[0005] Conventionally, glass fibers are produced as follows: glass is produced as a first step. Suitable raw materials are heated to temperatures ranging from 1100°C to 1500°C and converted into molten glass through a series of heat treatments and chemical reactions between various metal oxides, hydroxides and / or carbonates. Typically, the molten glass is then fractionated and left to solidify and form small glass, chunks or marbles, and stored for further use.
[0006] To produce the glass fibers, glass flakes, chunks, or marbles are fed into an electrically heated bushing that is equipped with an array of tipped orifices. The bushing is made of a precious metal alloy, and the temperature is precisely controlled to control the viscosity of the glass melt. The glass is melted and subsequently flows under gravity through the bushing and emerges from the tip of the bushing as attenuated glass fibers. The fibers are allowed to solidify and are typically wound onto a core to produce a bobbin containing the fibers.
[0007] No. 4,738,701 discloses a glass fiber forming assembly that allows for the rapid replacement of production fiber glass bushings. The system includes a secondary bushing and a means for heating it, as well as a glass delivery bushing that is permanently connected to the forehearth. The production bushing is not in physical contact with the forehearth. The assembly allows only one bushing at a time to be positioned adjacent to the glass passage tube of the forehearth. Summary of the Invention [Problem to be solved by the invention]
[0008] There is a need for improved methods for producing resorbable and biocompatible glass fibers which are more refined in that relatively fine fibers can be produced, preferably having a more uniform diameter in the sense that the coefficient of variation of the fiber diameter is low. [Means for solving the problem]
[0009] It has now been found that relatively fine glass fibers, preferably having a uniform fiber diameter, can be produced in a controlled manner using a process having a two-staged bushing design. The use of two bushings in series allows for the attenuation of fine fibers from the melt, producing fibers with fewer defects and bubbles. This results in a high quality glass fiber bundle having small diameter fibers with a uniform fiber diameter. The uniform fiber diameter is evidenced by a low coefficient of variation of the fiber diameter. The uniform fiber diameter also results in a stable process, resulting in a stable diameter over time.
[0010] First, a cold piece, chunk or marble of glass is melted in a first bushing, which is provided with a number of orifices through which the molten glass flows and is collected in the second bushing.
[0011] The melt is subsequently drawn from the second bushing through a plurality of orifices to produce fibers of a desired diameter, and the glass melt stream is allowed to solidify to obtain a glass fiber bundle.
[0012] By using this new method, a new resorbable, biocompatible, and preferably bioactive glass fiber bundle can be produced, specifically, a resorbable and biocompatible glass fiber bundle can be produced, characterized in that the glass fibers of the glass fiber bundle have an average diameter in the range of 5 to 30 μm, and the glass fiber bundle has a coefficient of variation of 15% or less.
[0013] The glass fiber bundles of the present invention, and glass fibers therefrom, can also be used in medical devices.
[0014] These glass fiber bundles and glass fibers therefrom are particularly suitable for the production of biocompatible, resorbable, preferably bioactive composites for use in the manufacture of medical devices, in which the glass fiber bundles according to the invention or the glass fibers therefrom are coated with and / or embedded in a polymer matrix, optionally after being provided with a sizing composition, which treatment makes them more compatible with the surrounding resorbable polymer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention relates to a resorbable and biocompatible glass fiber bundle (sometimes referred to as yarn), characterized in that the individual glass fibers in the glass fiber bundle have an average diameter of 5-30 μm. Preferably, the individual glass fibers (sometimes referred to as filaments) have an average diameter of 6-25 μm, more preferably 6-20 μm, more preferably 7-20 μm, even more preferably 8-15 μm. It is clear that the ranges also include the respective end points, i.e., average diameters of 5, 6, 7, 8, 15, 20, 25 and 30 μm. In this specification, the term "glass fiber bundle" is used in its ordinary sense and refers to a collection of aligned individual glass fibers that are somehow held together in close proximity. Glass fiber bundles are generally obtained in one attenuation step. Fiber bundles from different attenuation steps can be combined to form a cord. It is also possible to split one fiber bundle resulting from a single attenuation step into several bundles. It is understood that a glass fiber bundle can be produced according to the method of the invention using a two-staged bushing design. As a result, a glass fiber bundle according to the invention can refer to an assembly of glass fibers that is directly obtained or can be obtained by the method, without a fiber selection step being carried out.
[0016] It should be noted that the method of the present invention makes it possible to obtain glass fiber bundles in which the individual glass fibers are relatively fine, i.e., have a diameter of 30 μm or less, in particular 25 μm or less, more particularly 20 μm or less, in some embodiments 15 μm or less, and which have a low coefficient of variation, by the two-step bushing method described below. Without wishing to be bound by theory, it is believed that the use of two bushings as described below results in a more homogeneous glass melt, with fewer bubbles in the glass melt and therefore fewer voids in the fibers, which results in fewer fiber breakages.
[0017] The coefficient of variation of the diameter of the glass fibers in the glass fiber bundle is 15% or less, particularly 10% or less. The coefficient of variation may be 8% or less, or 6% or less. It has been found that in some embodiments the coefficient of variation may be 3% or less, which is a measure of the diameter being very uniform. The coefficient of variation is determined as follows: the diameters of 30 glass fibers from a glass fiber bundle are determined. The average diameter and standard deviation are calculated. The coefficient of variation is the standard deviation divided by the average diameter, expressed as a percentage.
[0018] The glass fiber bundle according to the invention preferably has at least 50 fibers, preferably at least 100 fibers, more preferably at least 150 fibers, even more preferably at least 200 fibers. As a maximum value, 5000 fibers, more particularly 3000 fibers, may be mentioned.
[0019] The glass fiber bundle according to the invention preferably has a linear density of 20 to 1300 tex, in particular 50 to 500 tex, preferably 70 to 300 tex, measured according to ASTM D1577-01 A. The term "linear density" corresponds to the weight of a length of the glass fiber bundle, the unit "tex" corresponding to the weight in grams per 1000 meters of the fiber.
[0020] Glass is always composed of various components. They are often divided into three categories: 1) network formers, 2) network modifiers, and 3) intermediates. Network formers are a class of components that form the highly cross-linked skeletal network that is the main component of the glass and gives the glass most of its properties. Network modifiers are a class of components that can be added to fine-tune the physical properties of the glass to meet certain specifications. Network modifiers usually reduce the glass network connectivity. There are also components that participate in the glass network and from which the glass properties can be fine-tuned. These components belong to the intermediates class.
[0021] The glass fiber bundle according to the invention preferably comprises glass fibers comprising a glass composition comprising a network former and a network modifier, wherein the molar ratio of the network former to the network modifier is between 1 and 4, preferably between 1.5 and 3.5, more preferably between 2 and 3. It has been observed that a ratio according to such a range, in particular one of the preferred ranges, results in good glass quality, in particular suitable for fiber formation.
[0022] The glass fibers are preferably made of oxides of silicon, such as silica (SiO), oxides of boron, such as diboron trioxide (B2O3) and boron suboxide (BO), and oxides of phosphorus, such as phosphorus trioxide (PO3) and phosphorus pentoxide (PO5 or PO4). 10 The glass fibers preferably contain a network former selected from the group consisting of oxides of sodium, such as Na2O or Na2O 2、 A network modifier selected from oxides of magnesium, such as MgO, and oxides of calcium, such as CaO.
[0023] More preferably, the glass fibres comprise some network formers and some network modifiers. The glass fibres preferably comprise: 50 to 75% by weight of SiO2, in particular 55 to 75% by weight, more in particular 60 to 75% by weight, 0-15% by weight of B2O3, 0.5 to 5% by weight of P2O5, in particular 0.5 to 4% by weight, more in particular 0.5 to 3% by weight, 5 to 20% by weight of Na2O, 0 to 25% by weight of CaO, in particular 2 to 25% by weight, more in particular 5 to 25% by weight, 0-10% by weight of MgO, 0-1 wt.% LiO, 0 to 15% by weight of K2O, in particular 0 to 10% by weight, more in particular 0 to 4% by weight, 0-4% by weight of SrO, 0-5 wt.% Al2O3, and 0-5% by weight Fe2O3 The composition comprises:
[0024] In one embodiment, the glass fiber has a composition including 60-75 wt.% SiO2, 0-15 wt.% B2O3, 0.5-3 wt.% P2O5, 5-20 wt.% Na2O, 5-25 wt.% CaO, 0-10 wt.% MgO, 0-1 wt.% Li2O, 0-4 wt.% K2O, 0-4 wt.% SrO, 0-5 wt.% Al2O3, and 0-5 wt.% Fe2O3.
[0025] In one embodiment, the glass composition comprises less than 10 wt.%, in particular less than 5 wt.% B2O3. In one embodiment, the glass composition comprises 7-20 wt.% Na2O. In one embodiment, the glass composition comprises 2-8 wt.% MgO. In one embodiment, the glass composition comprises 5-15 wt.% CaO.
[0026] The glass fibers of the present invention are preferably radiopaque, meaning that they are not transparent to X-rays. X-rays are understood to refer to high energy radiation having a wavelength of about 10 pm to about 10 nm. The use of radiopaque glass fibers is particularly attractive in composites for implantable medical devices, since it allows monitoring the degradation of the composite through X-rays in-vivo.
[0027] The glass fibres preferably have a tensile strength, measured by a tensile test according to DIN EN ISO 5079, of 1000 to 3000 MPa, preferably 1200 to 2500 MPa, more preferably 1400 to 2200 MPa.
[0028] The glass fibers in the glass fiber bundle according to the invention preferably have a modulus of elasticity of 20 to 100 GPa, preferably of 35 to 85 GPa, more preferably of 50 to 70 GPa, measured by a tensile test according to DIN EN ISO 5079 "Determination of breaking force and elongation at break of individual fibres" (ISO 5079:2020).
[0029] The glass composition in the glass fibers (and glass fiber bundles) preferably has a liquidus temperature, measured according to ASTM C829-81(2015), of at least 800° C., particularly at least 830° C., more particularly at least 860° C. The liquidus temperature is generally not more than 1000° C., particularly not more than 950° C., especially not more than 910° C.
[0030] In one embodiment, the glass composition melt has an operating window ΔT=T F -T L <330°C, where T Fis the fiber formation temperature at 3.0 dPas where log(η) is the fiber formation temperature, and T L is the liquidus temperature of the glass composition, in particular <280° C., more in particular <260° C. In particular, it has been found that the method of the invention makes it possible to obtain relatively fine glass fibres from a composition which has a relatively narrow working window.
[0031] The present invention further provides a method for producing glass fiber bundles in a controlled manner using a two-stage bushing design. In particular, the glass is refined in two separate stages to create a melt with fewer defects than glass produced using a single bushing stage. Such defects include air bubbles, which can be seen as voids in the solid glass using an optical microscope. Also, fibers with air bubbles are more likely to break, which can be seen during production as well as in laboratory tensile tests. In other words, therefore, glass produced with a two-stage design will form smaller diameter fibers of higher quality compared to a single bushing design. This results in a glass fiber bundle in which the glass fibers of the glass fiber bundle have an average diameter in the range of 5 to 30 μm when measured according to ASTM D1577-01 C and the glass fiber bundle has a coefficient of variation of up to 15%. The preferences expressed above regarding the properties of the glass fiber bundle and the glass fibers also apply to the glass fiber bundle produced by the method of the present invention and the fibers present therein. The preferences expressed above for the composition of the glass also apply to the glass used in the process and to the glass fibre bundles obtained through the process and the glass fibres present therein.
[0032] The present invention therefore relates to a method for obtaining glass fiber bundles, comprising the steps of: a) providing a resorbable and biocompatible glass composition melt; b) delivering the glass composition melt to a first bushing having a plurality of orifices; c) allowing or forcing the glass composition melt to flow through the plurality of orifices in the first bushing to create an intermediate glass melt stream; d) collecting the intermediate glass melt stream in a second bushing having a plurality of orifices and allowing or forcing the intermediate glass melt stream to obtain a second glass melt stream through the plurality of orifices of the second bushing; and e) attenuating the second glass melt stream from the plurality of orifices of the second bushing to obtain glass fibers, and solidifying the glass melt stream to obtain a glass fiber bundle. The above method further comprises the steps of:
[0033] After the glass fiber bundle is obtained, it is preferably recovered using a suitable device, preferably by winding the glass fiber bundle around a cylindrical cone.
[0034] In the first step of the method, cold glass pieces, chunks or marbles are melted in the first bushing to prepare a melt. The first bushing is provided with a number of orifices. Typically, the number of orifices ranges from 2 to 5000, in particular from 10 to 5000, in particular from 10 to 2000, more in particular from 20 to 2000. The orifices typically have a diameter in the range from 0.05 mm to 5 mm. In the first bushing, the melt is typically at a temperature of 1000 to 1500°C, more preferably from 1100 to 1400°C, even more preferably from 1250 to 1380°C, more in particular from 1250 to 1350°C.
[0035] The viscosity of the melt in the first bushing is 2000 poise or less, preferably 1000 poise or less, more preferably 850 poise or less or 750 poise or less, as measured according to DIN ISO 7884 1998-02. A relatively low viscosity helps to allow trapped air to escape. As a lower limit, 80 poise, in particular 100 poise, may be mentioned. It may be preferred that the viscosity in the first bushing is in the range of 100 to 500 poise, in particular 100 to 500 poise.
[0036] The glass composition in the first bushing can be allowed or forced to flow through the orifices in the first bushing to produce an intermediate glass melt stream, which is collected in the second bushing. The second bushing is provided with a plurality of orifices. Typically, the number of orifices is in the range of 10 to 5000, particularly in the range of 20 to 2000. The orifices typically have a diameter in the range of 0.05 mm to 5 mm. In the second bushing, the melt is typically at a temperature of 1100 to 1250°C.
[0037] The melt in the second bushing preferably has a viscosity of 2000 poise or less, preferably 1000 poise or less, more preferably 850 poise or less, as determined using DIN ISO 7884 1998-02. However, the viscosity is preferably at least 300 poise, more preferably at least 500 poise, and even more preferably at least 750 poise, to allow for a stable melt spinning process. In one embodiment, the glass melt has a liquidus temperature (T L ) and at the fiber formation temperature, the viscosity is higher than the lower limit of the fiberizing viscosity window.
[0038] Generally, the temperature of the second bushing will be lower than that of the first bushing, since the first bushing is operated at a temperature that produces a low viscosity melt that allows air to escape, while the second bushing provides a melt suitable for fiber production, which requires lower temperatures. Preferably, the temperature difference between the second bushing and the first bushing is at least 50°C, preferably at least 100°C, more preferably at least 150°C.
[0039] Similarly, the viscosity of the melt in the first bushing will generally be 50-800 poise lower than the fiber formation temperature viscosity in the second bushing. The viscosity of the melt in the first bushing may, for example, be 100-600 poise lower than the viscosity of the melt in the second bushing, preferably 200-400 poise lower than the viscosity of the melt in the second bushing, more preferably 250-350 poise lower than the viscosity of the melt in the second bushing, for example 310 or 320 poise lower than the viscosity of the melt in the second bushing.
[0040] It may be preferred that the diameter of the orifices of the second bushing is smaller than the diameter of the orifices of the first bushing, since the orifices in the second bushing are intended to feed thin glass fibers, whereas the orifices in the first bushing are only intended to pass the glass melt.
[0041] The homogeneity of the glass melt and the removal of air or gas from the glass melt can be improved by passing the intermediate glass melt flow over a plate between the first and second bushings in a thin film. This increases the surface area of the glass melt and increases its residence time. The plate can be provided as a separate device or it can be provided on top of the second bushing, upstream of the orifices in the second bushing, and / or below and downstream of the orifices in the first bushing. The thin film can be open in that the melt is provided on a carrier plate. It is also possible to provide the thin film between a carrier plate and a top plate. This intermediate thin film forming step provides additional degassing or degassing of the glass melt. It may be preferable for the thin film forming step to be performed at a temperature equal to or higher than the temperature of the first bushing.
[0042] The glass melt in the second bushing is allowed or forced to pass through the orifices of the second bushing to obtain the second glass melt stream, and the second glass melt stream from the orifices of the second bushing is attenuated to obtain fibers, and then the glass melt stream is solidified to obtain glass fiber bundles. These latter steps are conventional in the art and need not be described further.
[0043] In one embodiment, the method according to the invention further comprises dividing the glass fiber bundle into at least two parts, which can be attractive because it allows for a more precise selection of the weight and linear density of the glass fiber bundle.
[0044] In one embodiment, the fibers of the glass fiber bundle are sized. Sizing is well known in the art of glass fiber manufacturing. Sizing is a process in which fibers, in this case glass fibers, are treated with a surface-modifying composition. The sizing may contain various additives, such as plasticizers, film-forming polymers, or lubricants. In one embodiment, a sizing agent is applied that includes a thermoplastic, resorbable, and biocompatible polymer, such as a polyester, which is more preferably covalently bonded to the glass fibers via a coupling agent having at least one silane moiety. One reason for applying a sizing agent on glass fibers to be incorporated into a composite with a matrix polymer is to improve the interfacial adhesion between the glass fibers and the matrix polymer by improving the compatibility of the surface of the glass, which is generally hydrophilic in nature, with the hydrophobic matrix polymer in contact with the surface of the glass. Typically, the glass fibers are sized to reduce the surface energy. In the case of the concept of compatibility, the sizing layer is considered as an integral part of the glass fiber. As a result, a sized glass fiber that is compatible with the matrix polymer layer means that the sizing layer is compatible with the matrix polymer, and therefore provides good interfacial adhesion for load-transfer and proper distribution of the fiber in the matrix polymer. Thus, in a preferred embodiment, the resorbable glass fiber that is compatible with the matrix polymer is a resorbable glass fiber having a sizing layer on the surface that is compatible with the matrix polymer.An attractive sizing and method of application thereof is described in a patent application entitled "Resorbable glass fiber coated with a sizing and method for preparing such" having the same filing and priority date as this application, the text of which is incorporated herein by reference in its entirety. Additional sizing compositions are known in the art and need not be described further herein.
[0045] The glass fiber bundle according to the present invention and the glass fibers present therein are suitable for use in many applications.In one embodiment, the glass fiber bundle or the fibers derived from the glass fiber bundle are used in medical devices, such as orthopedic implants.Examples of orthopedic implants include bone fixation devices, intramedullary nails, joint (hip, knee, elbow) implants, spinal implants, and other devices for such applications, such as fracture fixation, tendon reattachment, spinal fixation, and spinal cages. Examples of bone fixation devices include screws, plates, rods, tapes, nails, wires, pin wires, anchors, cables, ties or wire ties, plate and screw systems, and external fixators. The coated glass fibers or composites of the present invention can also be used in tissue engineering, for example, in woven and nonwoven fabrics, and scaffolds. Thus, the present invention also relates to the use of glass fiber bundles and glass fibers in medical devices, and to medical devices comprising the composites described herein.
[0046] The present invention also relates to a composite comprising glass fiber bundles as described herein, or glass fibers derived from such bundles, in a polymer matrix. In particular, the polymer matrix is biocompatible and / or biodegradable. In the composite, the glass fibers or glass fiber bundles may be present as continuous fibers and / or chopped fibers. When chopped fibers are used, they generally have a length in the range of 1 mm to 50 mm, in particular 1 mm to 25 mm, more in particular 1 mm to 20 mm, even more in particular 2 mm to 10 mm, and most in particular less than 4 mm. The present invention also relates to a medical device comprising the composite.
[0047] Thus, in one embodiment, the present invention relates to a composite comprising glass fibers from one or more glass fiber bundles according to the present invention in a polymer matrix compatible with the glass fibers, said glass fibers and said polymer matrix being preferably biocompatible and resorbable, more preferably bioactive. As is well known in the art, bioactive materials are materials designed to induce or modulate biological activity. Bioactive materials are often surface-active materials that can chemically bond with mammalian tissue. Bioactive glasses may further be designed to elute ions or other chemicals that result in osteoconductive, osteoinductive, anti-infective and / or angiogenic benefits.
[0048] Examples of suitable polymer matrix materials are polylactide (PLA), poly-L-lactide (PLLA), poly-DL-lactide (PDLA), L-lactide / DL-lactide copolymer (PLDLA), polyglycolide (PGA), poly(ε-caprolactone) (PCL), copolymers of glycolide, copolymers of ε-caprolactone, copolymers of lactide, glycolide / trimethylene carbonate copolymer (PGA / TMC), lactide / tetramethylglycolide copolymer, lactide / trimethylene carbonate copolymer, lactide / δ-valerolactone copolymer, lactide / ε-caprolactone copolymer, glycolide / lactide copolymer (PGLA), lactide / glycol ... The polymers include polymers selected from the group consisting of ethylenediamine / trimethylene carbonate terpolymers, lactide / glycolide / ε-caprolactone terpolymers, PLA / polyethylene oxide copolymers, asymmetric 3,6-substituted poly-1,4-dioxane-2,5-diones, polyhydroxybutyrate (PHB), PHB / β-hydroxyvalerate copolymers (PHB / PHV), poly-β-hydroxypropionate (PHPA), poly-p-dioxanone (PDO) poly-δ-valerolactone-poly-ε-caprolactone, poly(ε-caprolactone-DL-lactide) copolymers, polyesters of oxalic acid, poly-β-malic acid (PMLA), poly-β-alkanoic acids, and mixtures thereof. The use of a matrix polymer selected from the group comprising polylactide, poly(lactide-co-glycolide), poly(lactide-co-ε-caprolactone), polyglycolide (PGA), and poly(ε-caprolactone) (PCL) may be particularly preferred.
[0049] Preferably, the composite has a glass fiber content, calculated on glass and polymer combined, of 5-95% by weight, preferably 10-90% by weight, more preferably 15-80% by weight, even more preferably 20-70% by weight, and most preferably 30-60% by weight. Alternatively, the composite preferably has a glass fiber content of at least 60% by weight, more preferably at least 70% by weight, even more preferably at least 80% by weight, and even more preferably at least 90% by weight.
[0050] The composite according to the invention may contain, in addition to the glass fibers (bundles) and the polymer, further components, for example up to 30% by weight, up to 20% by weight, or up to 10% by weight. Examples of further components may be hydroxyapatite and calcium phosphates, such as tricalcium phosphates (TCP), e.g. β-TCP. It may be preferred that the composite contains an additive, such as an active pharmaceutical ingredient (API) or a mineral ingredient, embedded within the composite.
[0051] The present invention also relates to a medical device comprising a glass fiber bundle according to the invention or a composite according to the invention. An attractive composite is described in a patent application having the same applicant, inventor and filing date as the present application, entitled "Biocompatible and resorbable polymer composite material and method for obtaining such", the text of which is incorporated herein by reference in its entirety.
[0052] In one embodiment, the medical device comprises a unidirectional composite tape. Glass fiber-based tapes are known in the art. They comprise a biodegradable polymer and a plurality of continuous glass fibers aligned in one direction, where the fibers are aligned along the length of the tape. The tape generally has a width of at least 2 times, particularly at least 5 times, more particularly at least 10 times, the thickness of the tape. The length of the tape generally is at least 10 times, particularly at least 100 times, the width of the tape. The thickness of the tape is preferably less than 0.3 mm, more preferably less than 0.2 mm, even more preferably less than 0.15 mm. The length of the tape is preferably at least 1 m, more preferably at least 5 m, even more preferably at least 10 m. The third dimension (i.e., width) is preferably 0.5 to 10 cm, more preferably 0.8 to 5 cm, even more preferably 1 to 2.5 cm. A composite tape can be obtained, for example, by spreading the fibers of a glass fiber bundle, contacting the glass fibers with a liquid polymer matrix and solidifying the matrix. Unidirectional composite tapes preferably have a matrix content of 2-40% by weight, in particular 5-30% by weight, more in particular 5-25% by weight, in a particular embodiment 10-20% by weight. As regards the nature of the matrix and the nature of the glass fibers, the preferred embodiments mentioned elsewhere also apply here.
[0053] In one embodiment, the medical device comprises multiple layers, each layer comprising a composite tape.
[0054] Thus, in one embodiment, the composite is molded in the form of a unidirectional composite tape, as described above. In alternative embodiments, the composite is molded as strands, (cannulated) rods, tubes, pellets, or granules. Strands / rods are round-shaped fiber-reinforced polymers with a diameter of preferably 5 to 50 mm. Pellets are small pieces of rod length with a diameter of about 5 to about 50 mm, and granules are small particles with a diameter of about 1 to about 10 mm. The dimensions of the pellets or granules may be adapted to match the dimensions of the feed screw used in polymer processing techniques, such as injection molding.
[0055] In composites and medical devices, the glass fiber (bundles) are preferably sized glass fiber (bundles).
[0056] As will be clear to one skilled in the art, different embodiments of the invention can be combined as long as they are not mutually exclusive.
[0057] All percentages used herein are by weight unless otherwise specified.
[0058] When amounts, concentrations, dimensions, and other parameters are expressed in the form of ranges, preferred ranges, upper values, lower values, or preferred upper and lower values, it is to be understood that any range that can be obtained by combining any upper value or preferred value with any lower value or preferred value is also specifically disclosed, regardless of whether the resulting range is expressly stated in the context.
[0059] The present invention will now be illustrated with reference to the following examples, without being limited thereto or by them.
[0060] Working Example
[0061] measurement
[0062] Average Fiber Diameter The average fiber diameter of the glass fibers in the glass fiber bundle is measured in accordance with ASTM D1577-01C.
[0063] X-ray fluorescence analysis (XRF) XRF analysis of the glass elements was carried out according to DIN 51001:2003-8.
[0064] X-ray diffraction (XRD) XRD analysis of amorphous content was performed according to ASTM F1538-03.
[0065] Glass fiber bundle weight Glass fiber bundle weight is measured according to ASTM D1577-01, Option A, using an ILE Yarn Reel, where one revolution of the steel reel corresponds to one meter of fiber.
[0066] Linear density and fiber diameter Linear density was determined according to ASTM D1577-01, option C-1, using a Textechno Favimat. This method is based on the string vibration technique, where the gauge length and pre-tensioning force are controlled and the resonance frequency is determined, which can then provide values for the linear density and diameter of the fiber.
number
[0067] The fiber diameter is the linear density T t can be calculated using the following formula:
number
[0068] Coefficient of variation The coefficient of variation is determined as follows: the diameters of 30 glass fibers in a glass fiber bundle are determined. The average diameter and standard deviation are calculated. The coefficient of variation is the standard deviation divided by the average diameter and is expressed in %.
[0069] liquidus temperature The liquidus temperature measurements were performed according to ASTM C829-81(2015).
[0070] viscosity The viscosity (η) was determined according to DIN ISO 7884 1998-02 "Glass-Viscosity and viscometric fixed points - Part 2: Determination of viscosity by means of rotation viscometers".
[0071] Tensile strength of glass fiber Tensile tests are carried out to determine the strength, modulus and maximum elongation of the fibers. Tensile measurements of single fibers are carried out at room temperature of 23° C. using a Textechno Favimat device equipped with a load cell of 210 cN. The tensile tests are carried out according to DIN EN ISO 5079. The gauge length is 20 mm and the test speed is 5 mm / min.
[0072] Example 1
[0073] The raw materials (sand, sodium carbonate, calcium carbonate, magnesium carbonate, sodium tetraborate, and calcium hydrogen phosphate dihydrate) were collected in platinum crucibles and subsequently melted in a furnace, then annealed, crushed, remelted, and annealed again to obtain a bioactive, resorbable, and biocompatible glass composition that was cooled and found to have a composition of 68.5 wt. % SiO, 1.5 wt. % PO, based on the average of three XRF measurements. 5、 2.1% by weight of B2O 3、 A glass piece was obtained containing 13.8 wt.% Na2O, 4.7 wt.% MgO, 9.2 wt.% CaO, 0.1 wt.% Al2O3, 0.022 wt.% Fe2O3, 0.008 wt.% K2O and 0.011 wt.% TiO2.
[0074] Example 2
[0075] A portion of the glass pieces obtained in Example 1 was loaded into a glass hopper and fed into a first bushing maintained at a temperature of 1288°C, where they were melted. The molten glass passed through the orifices of the first bushing. The glass melt was then flowed onto a plate where it was spread into a thin film, resulting in a homogenous and degassed glass composition. A thin film of molten glass was fed onto the top of a second bushing. The second bushing was maintained at a temperature of 1137-1193°C, as specified in Table 1 below for the various experiments. The second bushing was equipped with a base plate with 576 individual orifices, through which the molten glass was formed into a glass fiber bundle, and the filaments were wound on a winder with a collet diameter of 8 inches (203 mm). A sizing agent was applied to the filaments of the glass fiber bundle using a sizing applicator roller, and the glass fiber bundle was collected on a rotating core.
[0076] The fiber bundle weight and fiber diameter of the glass fibers were determined and are shown in Table 1 below. As can be seen, the fiber diameter could be manipulated by adjusting the winding speed of the collet and the temperature in the second bushing, and thereby the glass viscosity. At a constant temperature, the faster the pull speed, the smaller the resulting fiber diameter.
[0077] [Table 1]
[0078] Comparative example A
[0079] Another portion of the glass pellets obtained in Example 1 was loaded into a glass hopper and fed into a single bushing maintained at a temperature of 1150° C. The bushing had 204 individual orifices through which the molten glass was formed into a glass fiber bundle, and the filaments were wound on a winder with a collet diameter of 8 inches (203 mm). A sizing agent was applied to the fibers of the glass fiber bundle using a sizing applicator roller, and the glass fiber bundle was collected on a rotating collector.
[0080] The resulting melt was observed to be less homogeneous than the melt in Example 2. The resulting glass fibers exhibit more melt defects (e.g., crystals, bubbles). The fiber bundle weight was 66 tex. The fiber diameter was 11.2 microns. The coefficient of variation was 21.4%. From this data it can be seen that the process of the present invention in which two bushings are used results in fibers with a more uniform diameter, as evidenced by the lower coefficient of variation, than the equivalent process in which a single bushing is used.
[0081] Example 3
[0082] Example 2 was repeated, except that after collecting the fibers on a core according to Example 2, the fiber bundle obtained in Example 2 was collected on two or three separate cores arranged side by side to produce a bundle with a lower fiber bundle weight. The fiber bundle weight, single fiber diameter, tensile strength and modulus (including standard deviation) were measured and are shown in Table 2 below. Data for the unsplit sample FL-004 from Table 1 is also included.
[0083] [Table 2]
[0084] * The standard deviation for tensile strength is relatively high, which may be due to problems with sizing application.
[0085] Example 4
[0086] This example is intended to show that the method of the present invention makes it possible to obtain relatively fine fiber bundles from a glass composition that has a relatively narrow working window.
[0087] The liquidus temperature and fiber forming temperature were determined for the three glass compositions. The working window, i.e., the liquidus temperature T at which log(η) is 2.8 dPas, L and the fiber formation temperature T F The temperature difference (ΔT) between the temperature at the surface and the temperature at the surface was also calculated. The data is given in Table 3 below.
[0088] [Table 3]
[0089] From these compositions, fibers were produced using a process of the invention similar to that described in Example 2. For all compositions, it was found possible to obtain bundles of 500-600 high quality fibers with average diameters in the range of 6-30 microns.
Claims
1. 1. A resorbable and biocompatible glass fiber bundle, wherein the glass fibers of the glass fiber bundle have an average diameter in the range of 5 to 30 μm, and wherein the glass fiber bundle has a coefficient of variation of 15% or less.
2. 2. The glass fiber bundle according to claim 1, wherein the average diameter of the glass fibers of the glass fiber bundle is in the range of 6 to 20 μm.
3. 3. The glass fiber bundle according to claim 1 or 2, wherein the coefficient of variation of the glass fiber diameter is 10% or less, preferably 8% or less, or 6% or less, and in some embodiments 3% or less.
4. 4. The glass fiber bundle according to claim 1, wherein the number of fibers in the glass fiber bundle is at least 50, preferably at least 100, more preferably at least 150, even more preferably at least 200, and / or up to 5000, more particularly up to 3000.
5. The glass fiber bundle is a resorbable, biocompatible, preferably bioactive glass fiber bundle, wherein the glass fibers in the glass fiber bundle are 50-75% by weight of SiO 2 , 0-15% by weight B 2 O 3 , 0.5-5% by weight P 2 O 5 , 5-20% by weight of sodium 2 O. 5 to 25% by weight of CaO, 0-10% by weight of MgO, 0-1% by weight Li 2 O. 0-15% by weight K 2 O. 0-4% by weight of SrO, 0-5% by weight Al 2 O 3 , and 0-5% by weight Fe 2 O 3 The glass fiber bundle according to any one of claims 1 to 4, comprising:
6. 6. The glass fiber bundle according to claim 1, wherein the glass fibers have a tensile strength, measured according to DIN EN ISO 5079, of 1000 to 3000 MPa, preferably 1200 to 2500 MPa, more preferably 1400 to 2200 MPa.
7. 7. The glass fiber bundle according to claim 1, wherein the glass fibers have an elastic modulus, measured according to DIN EN ISO 5079, of 20 GPa to 100 GPa, preferably 35 to 85 GPa, more preferably 50 to 70 GPa.
8. a) providing a resorbable and biocompatible glass composition melt; b) delivering the glass composition melt to a first bushing having a plurality of orifices; c) permitting or forcing the glass composition melt to flow through the plurality of orifices in the first bushing to create an intermediate glass melt stream; d) collecting the intermediate glass melt stream in a second bushing having a plurality of orifices, and allowing or forcing the intermediate glass melt stream to obtain a second glass melt stream through the plurality of orifices of the second bushing; and e) attenuating the second glass melt stream from the plurality of orifices of the second bushing to obtain fibers, and solidifying the glass melt stream to obtain a glass fiber bundle. The process includes the steps of: A method for obtaining glass fiber bundles, in particular glass fiber bundles according to any one of claims 1 to 7.
9. 9. The method of claim 8, wherein the temperature at the first bushing is in the range of 1000 to 1500°C and the temperature at the second bushing is in the range of 1100 to 1250°C.
10. 10. The method according to claim 8 or 9, wherein the second bushing is operated at a lower temperature than the temperature of the first bushing, wherein the difference between the temperature of the second bushing and the temperature of the first bushing is at least 50°C, preferably at least 100°C, more preferably at least 150°C.
11. The method of any one of claims 8 to 10, wherein the viscosity of the melt in the first bushing is at least 50 poise lower than the viscosity of the melt in the second bushing.
12. 12. The method according to claim 8, wherein the intermediate glass melt stream originating from the plurality of orifices in the first bushing is passed in a thin film over a plate before being fed into the second bushing.
13. The method of claim 12 , wherein the temperature of the glass in the film is greater than the temperature of the glass in the first bushing.
14. 14. The method of any one of claims 8 to 13, further comprising splitting the glass fiber bundles into at least two bundles, and / or applying a sizing to one or more of the glass fiber bundles, and / or collecting one or more of the glass fiber bundles.
15. A composite comprising a glass fibre bundle according to any one of claims 1 to 6, or obtained by the method according to any one of claims 8 to 14, or comprising glass fibres from said glass fibre bundle in a polymer matrix compatible with said glass fibres (bundles), said glass fibres and said polymer matrix being preferably biocompatible, resorbable, more preferably bioactive.
16. 16. A composite according to claim 15 in the form of a unidirectional composite tape or in the form of strands, (cannulated) rods, tubes, pellets or granules, in particular in the form of a unidirectional tape.
17. 17. A medical device comprising a glass fiber bundle according to any one of claims 1 to 7, or comprising a glass fiber bundle obtained by the method according to any one of claims 8 to 14, or comprising glass fibers from said glass fiber bundle, or comprising a composite according to claim 15 or 16.
Citation Information
Patent Citations
Multi-screen device for mixing glass streams in glass bushings
JP2001513478A
Bushing for glass fiber
JP2002128538A
Glass composition for glass fiber, glass fiber and glass fiber sheet-like material
JP2009286686A
Glass fiber, method for manufacturing glass fiber, and glass fiber sheet-like object
JP2011068549A
Biodegradable, bioactive and biocompatible glass compositions
JP2022505779A